Shock qualification of low-cost blast resistant wheels by in field tests. Issue 4 (December 2022) - Silvestri, Paolo; Naselli, Giovanna Adele; Cepolina, Emanuela Elisa; Zoppi, Matteo
This paper presents the results obtained during an experimental campaign on blast resistant wheels designed for a low-cost demining machine, derived from an agricultural tractor. Such wheels must fulfil two requirements: first, they have to be able to retain their mechanical integrity in case of blast and still work after one or more explosions, in order to be able to drive the machine out of the minefield without human intervention; second, they must reduce as much as possible the amount of energy transferred to the vehicle, to protect the on-board equipment from the effect of the detonation of a landmine. One of the goals of the experimental activity was to compare two wheels characterized by different designs. Mechanical performance and capacity of the wheels to reduce the energy transferred to the vehicle have been assessed to verify whether the wheels were suitable for the task and to identify which wheel performs best. Physical integrity of both wheels was assessed by visual inspection after each explosion. To evaluate the energy transferred to the vehicle, a measurement of the potential energy transferred, by means of a ballistic pendulum, equipped with an encoder, was performed together with a triaxial acceleration measurement in correspondence of the wheel hub. The triaxial accelerometer measurement was then also used to assess the behaviour of the wheels mounted on the vehicle after tests on the ballistic pendulum. Wheel performances have been quantified using specific features and frequency domain functions, related to the damage induced by the vibration at the interface between the hub and the demining machine. The obtained results suggest that the heaviest wheel performs better both in terms of mechanical integrity and of shock response.